DOI: 10.18297/etd/825
|View full text |Cite
|
Sign up to set email alerts
|

Novel processes for large area gallium nitride single crystal and nanowire growth.

Abstract: Li, Hongwei 1975-, "Novel processes for large area gallium nitride single crystal and nanowire growth." (2005 I was born in a small, typical rural village in China. I couldn't remember but I could imagine the hardness my parents experienced at that time when people were still struggling for adequate food and clothing. I survived from twice serious drown when I was 2-3 years old, but resulted in serious cough from the accidents. My parents worried about me, spent every penny they had to try every recipe they c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 109 publications
(142 reference statements)
0
2
0
Order By: Relevance
“…The author suggested that the incorporation of nitrogen into the Ga melt induced the spreading behavior of the metal onto the quartz substarte. 147 In a similar manner, additions of others metals like, bismuth (Bi), tin (Sn), and indium (In) to Ga have been shown to reduce the surface tension of the alloy compared to that of pure Ga. 148 Moreover, Kleinbaum et al, who obtained GaN films via plasma-assisted LPE, stated that the ability of Ga to wet a surface is increased by adding hydrogen to the nitrogen plasma.…”
Section: Wetting Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The author suggested that the incorporation of nitrogen into the Ga melt induced the spreading behavior of the metal onto the quartz substarte. 147 In a similar manner, additions of others metals like, bismuth (Bi), tin (Sn), and indium (In) to Ga have been shown to reduce the surface tension of the alloy compared to that of pure Ga. 148 Moreover, Kleinbaum et al, who obtained GaN films via plasma-assisted LPE, stated that the ability of Ga to wet a surface is increased by adding hydrogen to the nitrogen plasma.…”
Section: Wetting Propertiesmentioning
confidence: 99%
“…This conclusion is in good agreement with previous studies. 140,[146][147] An example of a Ga droplet exposed to nitrogen is presented in…”
Section: Wetting Propertiesmentioning
confidence: 99%